Mesenchymal Stromal Cells and Neural Stem Cells Potential for Neural Repair in Spinal Cord Injury and Human Neurodegenerative Disorders - Cizkova, Dasa; Zilka, Norbert; Kazmerova, Zuzana; Slovinska, Lucia; Vanicky, Ivo; Novotna-Grulova, Ivana; Cigankova, Viera; Cizek, Milan; Novak, Michal (IntechOpen, 2012)
None